“I Can Read These Colors.” Orthographic Manipulations and the Development of the Color-Word Stroop - Arsalidou, Marie; Agostino, Alba; Maxwell, Sarah; Taylor, Margot J. (Frontiers in Psychology, 2013)
The colour-word Stroop is a popular measure in psychological assessments. Evidence suggests that Stroop performance relies heavily on reading, an ability that improves over childhood. One way to influence reading proficiency is by orthographic manipulations. To determine the degree of interference posed by orthographic manipulations with development, in addition to standard colour Words (purple) we manipulated letter positions: First/last letter in correct place (prulpe) and Scrambled (ulrpep). We tested children 7 to 16 years (n =128) and adults (n = 23). Analyses showed that Word- and First/last-incongruent were qualitatively similar, whereas Word-congruent was different than other conditions. Results suggest that for children and adults, performance was hindered the most for incongruent and incorrectly spelled words and was most facilitated when words were congruent with the ink colour and correctly spelled. Implications on visual word recognition and reading are discussed.